Absorbers analysis for anechoic chamber - Ngah, Razali (Penerbit UTM Press, 2000)
The most important element in an anechoic chamber is absorbers. Absorbers will absorb an electromagnetic wave to provide nonreflecting environments sir to outer space. Absorbers have been deveiL it Radio Science Laboratory, Faculty of EJ. .:al Engineering, UTM, consisting of absorbing material in pyramid shape, carbon powder and coating liquid (paint). Absorbers are coated with carbon using oil and water-based paint. This paper highlights the design and construction of the absorbers, as well as the measurement system configuration for absorption measurements. The result is compared with those of commercially available absorbers.